2017
DOI: 10.3847/1538-4357/aa927b
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Atmospheres of Known Temperate Earth-sized Planets with JWST

Abstract: Nine transiting Earth-sized planets have recently been discovered around nearby late M dwarfs, including the TRAPPIST-1 planets and two planets discovered by the MEarth survey, GJ 1132b and LHS 1140b. These planets are the smallest known planets that may have atmospheres amenable to detection with JWST. We present model thermal emission and transmission spectra for each planet, varying composition and surface pressure of the atmosphere. We base elemental compositions on those of Earth, Titan, and Venus and cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
367
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(386 citation statements)
references
References 88 publications
(104 reference statements)
15
367
2
2
Order By: Relevance
“…-Habitable case 1 (Hab1): In this case, constituted of a modern Earth-like atmosphere of 1 bar of N 2 and 400 ppm of CO 2 , the dynamical core, the clouds and atmospheric processes are tested together. It is also the most widespread benchmark for habitable planets in the literature (Barstow and Irwin, 2016;Morley et al, 2017;Lincowski et al, 2018).…”
Section: Atmospheric Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Habitable case 1 (Hab1): In this case, constituted of a modern Earth-like atmosphere of 1 bar of N 2 and 400 ppm of CO 2 , the dynamical core, the clouds and atmospheric processes are tested together. It is also the most widespread benchmark for habitable planets in the literature (Barstow and Irwin, 2016;Morley et al, 2017;Lincowski et al, 2018).…”
Section: Atmospheric Configurationsmentioning
confidence: 99%
“…OLR and ASR correspond to outgoing longwave radiation (at TOA) and absorbed shortwave radiation (at TOA), respectively, SW and LW correspond to shortwave and longwave, respectively, CF corresponds to cloud fraction and MMR at mass mixing ratio. The main objective of THAI is to highlight how differences in atmospheric profiles produced by each GCM are going to impact the predictions of atmosphere detectability and observational constraints for habitable planet targets such as TRAPPIST-1e (Morley et al, 2017;Fauchez et al, 2019). Therefore, in addition to the parameters of Table 3, we will emphasize the differences between the models in term of the planet's climate and habitability with a particular attention on the cloud coverage.…”
Section: Model Spatial Resolutions and Time Stepsmentioning
confidence: 99%
“…However, infrared spectroscopy mainly probes high atmospheric layers, which would correspond to the stratosphere and mesosphere on Earth (p 0.1 bar or altitudes greater than 20 km, see e.g. Barstow & Irwin (2016); ⋆ E-mail: carone@mpia.de (LC) Kreidberg & Loeb (2016); Morley et al (2017)). To discuss habitability, we have to reliably infer the properties of the underlying troposphere and potentially habitable surface from upper atmosphere composition derived from infrared spectra.…”
Section: Introductionmentioning
confidence: 99%
“…These authors have shown that 1.4 bars of photospheric pressure is needed to explain the derived heat redistribution efficiency value. The profiles are constructed analytically, following a dryadiabatic profile from the surface of 1.4 bars to 0.1 bars and continuing in isothermal fashion until 10 −7 bar (Morley et al 2017;Miguel 2019). This is done using 120 equally spaced log atmospheric layers.…”
Section: Planetary Properties and Thermal Profilesmentioning
confidence: 99%